Positive Dicipline Parenitng: Mathematics Learning Strategies for Elementary School Students Self-Confidence - Malik Ibrahim; Puji Yanti Fauziah; Riana Riana; Guldana Muzdybayeva (Universitas Muhammadiyah Mataram, 2024)
Mathematics is still a challenge for students in learning both at school and at home. Children tend to feel insecure when learning mathematics. This research aims to determine the effect of positive disciplinary parenting in mathematics learning on elementary school students' self-confidence. The research method uses quantitative research with an ex post facto design, where research data on learning outcomes uses semester grades in mathematics subjects. The research sample was 30 students from 3 schools taken randomly with taken using a quota sampling technique from each school was determined to have 10 students. Data collection uses learning outcomes tests and student self-confidence questionnaires. The results of the research show a sig value > 0.031 and an F value of 11,774, which means that there is a significant relationship between positive discipline parenting and students' self-confidence in elementary school students' mathematics learning. Apart from that, the results of the student self-confidence questionnaire were in the very high category at 90% and in the high category at 85%, meaning that elementary school students have an average of high self-confidence in learning mathematics with positive disciplinary parenting. Thus, the results of this research need to be taken into consideration by parents and educational institutions collaborating in assisting students to develop self-confidence in learning.